Blood pressure variability and the development of early neurological deterioration following acute ischemic stroke. Issue 10 (October 2015) - Chung, Jong-Won; Kim, Nayoung; Kang, Jihoon; Park, Su Hyun; Kim, Wook-Joo; Ko, Youngchai; Park, Jung Hyun; Lee, Ji Sung; Lee, Juneyoung; Yang, Mi Hwa; Jang, Myung Suk; Oh, Chang Wan; et al.
Abstract : Objectives: Early neurological deterioration (END) is a common condition associated with poor outcome after acute ischemic stroke. We studied association between blood pressure (BP) variability and development of END. Methods: In this retrospective observational study, we studied a consecutive series of patients hospitalized for acute ischemic stroke within 24 h of onset. The primary outcome of interest was the development of END according to predefined criteria within the first 72 h of stroke onset. During this period, the mean, maximum (max), and minimum (min) values for the SBP and DBP were measured. The following parameters of BP variability were calculated for the SBP and DBP: the difference between the maximum and minimum (max−min), the SD, and the coefficient of variation. Results: Of the 1161 patients enrolled in the study (mean age, 67.5 ± 13.3 years; 59.6% men), 210 (18.1%) developed END. All of the BP variability parameters were linearly associated with END independent of mean BP and potential clinical variables ( P values < 0.05 on likelihood ratio tests for trend), except for SBPmax−min. Among the other BP parameters, SBPmean, SBPmax, DBPmax, and DBPmin were independently associated with END. After adjustments for potential confounders, the odds for END increased 14–21% with each increase of one standard deviation in the BP variability parameter. Conclusion: BP variability is independently and linearly associated with the development of neurologic deterioration in acute stage of ischemic stroke. Abstract : Supplemental Digital Content is available in the text